Efficacy of Some Botanicals against Potato tuber moth, Phthorimaea operculella (Zeller, 1873) - Niroula, S.P.; Vaidya, Kamini (Our Nature, 2006)
Dried powders of five different plants, rhizomes of Acorus calamus, leaves of Melia azedarach, ripen berries of Piper longum, leaves of Prunus persica and ripen fruit of Lindera neesiana were tested as treatments for the control of potato tuber moth at laboratory. Three concentrations C1 0.05%w/w, C2 0.5%w/w and C3 5%w/w were used in each treatment. The percentage mortality of adult PTM in each treatment was observed at every 24 hours of one week and compared with control. The effects of the treatment were also studied up to first generation constructing the life table. All the concentration of L. neesiana and A. calamus were found effective in PTM control. L. neesaina showed 66.7%, 70.0% and 83.3% and A. calamus 56.7%, 66.7% and 70% adult mortality, 168 hours after treatment in C1, C2and C3 concentrations. The effects of these two treatments persist for long periods, which causes high percentage mortality of larvae and less adult emergence in first generation. Keywords: Phthorimaea operculella, Lindera neesiana, Acorus calamus doi:10.3126/on.v2i1.320 Our Nature (2004) 2: 21-25